1994
DOI: 10.1002/cne.903440407
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of retinal ganglion cell axon arbor size by target availability: Mechanisms of compression and expansion of the retinotectal projection

Abstract: The ability of pre- and postsynaptic populations to achieve the proper convergence ratios during development is especially critical in topographically mapped systems such as the retinotectal system. The ratio of retinal ganglion cells to their target cells in the optic tectum can be altered experimentally either by early partial tectal ablation, which results in an orderly compression of near-normal numbers of retinal projections into a smaller tectal area, or by early monocular enucleation, which results in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The LGN axons compete for neurotrophic factors released by the post-synaptic cells. Such fixed pre- and post-synaptic resources in the RGCs of gold fish (Hayes and Meyer, 1988) and optic tectum cells (Xiong et al, 1994) are reported in the literature.…”
Section: Methodsmentioning
confidence: 81%
“…The LGN axons compete for neurotrophic factors released by the post-synaptic cells. Such fixed pre- and post-synaptic resources in the RGCs of gold fish (Hayes and Meyer, 1988) and optic tectum cells (Xiong et al, 1994) are reported in the literature.…”
Section: Methodsmentioning
confidence: 81%
“…Volume measurements of HRPlabeled terminal fields are an overall measure that do not necessarily equate to equal densities of terminal connections. Measurements of individual arbors and terminal bouton numbers would be necessary to examine RGC arbors at the single cell level (Xiong et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…vLGN, ventral lateral geniculate nucleus; dLGN, dorsal lateral geniculate nucleus; PT/LP, pretectal/lateral posterior nucleus complex; SC, superior colliculus. mal bouton density (Xiong et al, 1994). As a result, normal electrophysiological function can be maintained over a wide range of convergence ratios such as would occur after orderly compression of the retino-collicular projection (Finlay et al, 1979a;Xiong et al, 1994).…”
Section: Direct Compensationmentioning
confidence: 97%
“…More commonly however neurons make connections to many other neurons (i.e., they have a large axonal "fan-out") and receive large numbers of incoming connections (dendritic "fan-in"). As two examples, Xiong et al [10] found an average fan-out of 167 for retinal ganglion cells in the tectum of the hamster, while Palkovits et al [11] found an average fan-in of 85 000 onto the Purkinje cells of the cat. In order to implement arbitrary many-to-many network connectivity, address-events are commonly received not directly by a neural array chip but rather by a microcontroller, and are then compared to a lookup table in memory in order to find out the addresses of the neurons or synapses which should be targeted.…”
Section: Introductionmentioning
confidence: 98%